An Analysis of Code Mixing of an Australian Youtuber â€œDave Jephcottâ€ in His Instagram â€œLondo Kampungâ€ (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2021)
Code mixing is a phenomenon in the form of the use of elements from a particular language in one sentence or another language discourse. The objective of this research is to find out the type of code-mixing uttered by an Australian Youtuber in his Instagram â€œLondo Kampungâ€. This study uses a descriptive qualitative method. In Instagram â€œLondo Kampungâ€. It is found the mixing of various linguistic units in the grammatical system within a sentence. There are some types of insertion of code-mixing, such as in elements of word, phrase, clause, hybrid, and repetition. There 182 code mixing found in Instagram captions. In insertion of the word shows 114 data or 62.64% which consist word class of noun and adjective. In insertion of hybrid shows 36 data (19.78 %), such as in insertion suffix both in Indonesian and Javanese, also prefix both in Indonesian and Javanese. In phrase shows 14 data (7.69 %) which consist of the noun phrase and adjective phrases. In insertion of the clause shows 12 data (6.59 %), and in repetition shows 6 data (3.33 %) which consist independent clause. The most dominant type insertion of code-mixing is in the element of words. Code mixing here occurs when the speaker (Dave Jephcott) inserts an element of a foreign language (English) in an utterance when he mostly communicates in written in his first language (Javanese and Indonesian).